Accumulation of ph1 (zip4-5B) and ph2 (msh7-3D) mutations fails to boost homoeologous recombination in hexaploid wheat - Haquet, Camille; Nadaud, Isabelle; Martin, Azahara C.; Rey, Maria-Dolores; Ben Bouslah, Asma; John-Bejai, Carus; Moore, Graham; Sourdille, Pierre (Frontiers in Plant Science, 2026)
Diversification of the hexaploid (bread) wheat genetic pool using wild genetic resources relies on effective meiotic recombination (crossover) between wheat chromosomes and their counterparts from related species (homoeologues). However, crossover between homoeologues is normally suppressed by two major genes, ZIP4-5B (Ph1) and MSH7-3D (Ph2). We investigated the effect of introducing zip4-5B and/or msh7-3D mutations into interspecific hybrids derived from crosses between wheat and Aegilops variabilis. Single and double mutants were exploited in Chinese Spring (CS) and Cadenza (Cad) genetic backgrounds, as well as in a CS/Cad recombinant background. Meiotic cells at metaphase I were scored for univalents, bivalents, and multivalents, from which chiasma numbers were deduced. We demonstrated a non-cumulative effect of simultaneous zip4-5B and msh7-3D mutations on homoeologous recombination, as homoeologous crossovers reached a maximum when ZIP4-5B alone was mutated. We also showed that hybrids carrying both the zip4-5B and msh7-3D mutations in the same genetic background exhibited a higher recombination rate compared to a double mutant in the CS/Cad recombinant background. The progression of meiosis was also monitored in the various interspecific hybrids mutants, revealing clear disruptions. Thus, our study provides key insights for optimizing the introgression of beneficial alleles from wild relatives into elite wheat germplasm; first by demonstrating the efficiency of ZIP4-5B and MSH7-3D mutations independently and in combination and second by elucidating the influence of the genetic background in which these mutations are present in an interspecific hybrid context.